Environmental Application of the BaPb0.9Sb0.1O3 Perovskite: Guaiacol Electrodegradation - Rodrigues,A. (2014)
The perovskite BaPb0.9Sb0.1O3 was prepared through the ceramic route and, after being chemical, structural and electrochemically characterized, it was used in the electrochemical oxidation of guaiacol, using Na2SO4 as electrolyte, at current densities of 5 and 10 mA cm-2 and initial guaiacol concentrations of 50, 100 and 200 mg L-1 . The guaiacol degradation was followed by UV-Visible absorbance measurements, Chemical Oxygen Demand (COD) tests and Dissolved Organic Carbon (DOC) analysis. The combustion efficiency was also determined. Results have shown COD removals between 40 and 85 % and DOC removals from 34 to 66 % after 120 h assays. The absolute COD and DOC removals increase with guaiacol initial concentration and applied current density. The mineralization tendency, measured as the combustion efficiency, was maximum for the applied current density of 10 mA cm-2 and a guaiacol initial concentration of 200 mg L-1.